2015
DOI: 10.5664/jcsm.4938
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Daylight Saving Time on Adolescents' Sleep and Vigilance

Abstract: Study Objectives: Daylight saving time (DST) has been established with the intent to reduce energy expenditure, however unintentional effects on sleep and vigilance have not been consistently measured. The objective of this study was to test the hypothesis that DST adversely affects high school students' sleep and vigilance on the school days following its implementation. Methods: A natural experiment design was used to assess baseline and post-DST differences in objective and subjective measures of sleep and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 34 publications
0
29
0
1
Order By: Relevance
“…The data presented for this manuscript represent daily diary assessments and sleep actigraphy data for a total of 294 reports. A sample size of 42 and a total number of ∼300 reports for this type of analysis is comparable to many published studies using daily actigraphy data and/or daily diaries of alcohol use among adolescents/young adults (e.g., (Geoghegan et al, 2012; Gerber et al, 2014; Medina, Ebben, Milrad, Atkinson, & Krieger, 2015; Pearson, D'Lima, & Kelley, 2013; Witkowski et al, 2015)).…”
Section: Methodsmentioning
confidence: 63%
“…The data presented for this manuscript represent daily diary assessments and sleep actigraphy data for a total of 294 reports. A sample size of 42 and a total number of ∼300 reports for this type of analysis is comparable to many published studies using daily actigraphy data and/or daily diaries of alcohol use among adolescents/young adults (e.g., (Geoghegan et al, 2012; Gerber et al, 2014; Medina, Ebben, Milrad, Atkinson, & Krieger, 2015; Pearson, D'Lima, & Kelley, 2013; Witkowski et al, 2015)).…”
Section: Methodsmentioning
confidence: 63%
“…Another explanation is that in Brazil, the daylight-saving time during Summer is only adopted in some regions (South, Southeast and Central). Studies have shown that removing one hour in daylight time may be harmful to sleep 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Clock timing based on Coordinated Universal Time (UTC) can vary from this circadian system by an hour or more because of time zones, daylight savings time (DST), traveling to another time zone and other factors. These UTC time variations from environmental cues must be eliminated when determining optimal timings, for example daylight saving time (Medina et al, 2015 ).…”
Section: Method: Neuroscience-based Theoretical Modelmentioning
confidence: 99%